The synergistic effects of polyphenols and intestinal microbiota on osteoporosis - Wang, Keyu; Hu, Siwang (Frontiers in Immunology, 2023)
Osteoporosis is a common metabolic disease in middle-aged and elderly people. It is characterized by a reduction in bone mass, compromised bone microstructure, heightened bone fragility, and an increased susceptibility to fractures. The dynamic imbalance between osteoblast and osteoclast populations is a decisive factor in the occurrence of osteoporosis. With the increase in the elderly population in society, the incidence of osteoporosis, disability, and mortality have gradually increased.Polyphenols are a fascinating class of compounds that are found in both food and medicine and exhibit a variety of biological activities with significant health benefits.As a component of food, polyphenols not only provide color, flavor, and aroma but also act as potent antioxidants, protecting our cells from oxidative stress and reducing the risk of chronic disease. Moreover, these natural compounds exhibit anti-inflammatory properties, which aid in immune response regulation and potentially alleviate symptoms of diverse ailments. The gut microbiota can degrade polyphenols into more absorbable metabolites, thereby increasing their bioavailability. Polyphenols can also shape the gut microbiota and increase its abundance. Therefore, studying the synergistic effect between gut microbiota and polyphenols may help in the treatment and prevention of osteoporosis. By delving into how gut microbiota can enhance the bioavailability of polyphenols and how polyphenols can shape the gut microbiota and increase its abundance, this review offers valuable information and references for the treatment and prevention of osteoporosis.